Η ΥΠΟΔΟΡΙΑ ΕΙΡΩΝΕΙΑ ΣΤΗ ΣΚΗΝΗ ΤΗΣ ΕΥΑΔΝΗΣ ΤΩΝ ΙΚΕΤΙΔΩΝ ΤΟΥ ΕΥΡΙΠΙΔΗ [THE LATENT IRONY IN EVADNE’S SCENE IN EURIPIDES’ SUPPLIANTS] - Mitta , Chrysanthi (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The purpose of this paper is to examine the latent irony in Evadne’s scene in Euripides’ Suppliants, which is woven within a web of allusions, contrasts, conflations, reflections, and blurred boundaries. Specifically, I focus on the conflation of marriage with death, the female Bacchic ecstasy, escape, and transgression, combined with the masculine mania of Ares and the consequent undermining or redefinition of social gender roles. The latter is also achieved by the tragic bride’s adoption of masculine values in the context of her ‘heroic’ suicide, as well as the mutual reflection of her husband, Capaneus, and her father, Iphis. Consequently, the focus of my research is the relationship between oikos and polis, the conflict but also the conflation of values and their meaning for each person, the power of emotion, and the effects of war on people. Furthermore, the ironic overtones are evident in the tension between the scene and the drama’s Eleusinian backdrop and its mythological frame.